2005
DOI: 10.4049/jimmunol.175.7.4408
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Induced Heme Oxygenase-1 Expression in Human Monocytic Cells Is Mediated via Nrf2 and Protein Kinase C

Abstract: Monocytes play a key role in mobilization of the immune response during sepsis. In response to LPS, monocytes produce both proinflammatory mediators and regulatory proteins that counteract the inflammation and oxidative stress. In murine macrophages, LPS stimulates expression of heme oxygenase 1 (HO-1), a cytoprotective enzyme that catalyzes the degradation of heme. The HO-1 5′-untranslated region, similarly to other cytoprotective genes, contains antioxidant-response elements (AREs) that can bind the transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
146
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(157 citation statements)
references
References 67 publications
9
146
2
Order By: Relevance
“…LPS is known to affect HO-1 expression in leukemic cell lines and monocytes. (19,(22)(23)(24) To understand the regulatory mechanism of HO-1 expression in leukemic cells, we compared the effect of LPS on HO-1 expression between the U937 cell line and CD14 + primary monocytes. LPS upregulated HO-1 in U937 cells, but this upregulation was not associated with an increase or decrease in Nrf2 or Bach1 levels in the whole cell lysates ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…LPS is known to affect HO-1 expression in leukemic cell lines and monocytes. (19,(22)(23)(24) To understand the regulatory mechanism of HO-1 expression in leukemic cells, we compared the effect of LPS on HO-1 expression between the U937 cell line and CD14 + primary monocytes. LPS upregulated HO-1 in U937 cells, but this upregulation was not associated with an increase or decrease in Nrf2 or Bach1 levels in the whole cell lysates ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(13)(14)(15)(16)(17)(18) Nrf2 plays an essential role in HO-1 gene regulation in human monocytes. (19,20) Tumor necrosis factor (TNF)-dependent HO-1 induction is mediated by the activation of Nrf2 in human myelomonocytic leukemic cell lines.(11) In contrast, we have previously shown that TNF suppresses HO-1 expression in peripheral monocytes by accelerating mRNA decay without affecting transcription activity.(21) Moreover, LPS positively or negatively regulates HO-1 expression in human and rodent monocytes and the human myelomonocytic leukemic cell line, THP-1. (19,(22)(23)(24) Bach1 is known to play an important role in cellular homeostasis.…”
mentioning
confidence: 99%
See 3 more Smart Citations